Analysis of changes in resources and outputs of companies and partnerships in Hungarian agriculture - Harangi-Rákos, Mónika (Acta Agraria Debreceniensis, 2011)
The aim of the study was to examine the achievement of Hungarian agricultural companies and partnerships, particularly agricultural co-operatives based on the aggregated database of National Tax and Customs Administration (NAV)1. From the methodological aspect, descriptive statistical methods and time series analysis were used. One of the most important conclusions is that the socio-economic weight of the agricultural co-operatives was strongly decreased in the period after the EU accession. The other important statement is that apart from the general examination of economic actors on aggregated level the comparative analysis of the single organizations forms would be needed. In the case of co-operatives, separated examination of the former type producer co-operatives and the so-called new type ones (e.g. marketing co-operatives etc.) would be necessary.